Persepsi Siswa Terhadap Penggunaan Whatsapp dalam Pembelajaran Bahasa Jerman - Eving Campiong; Wahyu Kurniati Asri; Mantasiah R (Indonesian Journal of Pedagogical and Social Sciences, 2022)
Abstract. This research is a descriptive type of research with a dual method approach, namely quantitative and qualitative, this study aims to determine students' perceptions of the use of Whatsapp in learning German. The data from this study were students' perceptions of the use of Whatsapp in learning German which were obtained from students in the form of questionnaires and interviews. Sources of data in this study were 70 students of SMA Negeri 5 Bulukumba. Based on the results of data analysis from the questionnaire, it showed that as many as 8 (11%) students who had the perception of strongly agreeing, 41 (61%) students who had the perception of agreeing, 20 (27%) students with the perception that it could not be determined, 1 (1%) students with the perception of disagreeing and there were no students who had the perception of strongly disagreeing, and the interview data conducted explained the various features possessed by Whatsapp that can support online learning such as voice messages, video calls and documents. It can be concluded that the perception of students of SMA Negeri 5 Bulukumba on the use of the Whatsapp application in learning German is agree. Keywords: Student Perception, Whatsapp, Learning